Biomarkers of coagulation and fibrinolysis in acute myocardial infarction: a joint position paper of the Association for Acute CardioVascular Care and the European Society of Cardiology Working Group on Thrombosis - Krychtiuk, Konstantin A.; Speidl, Walter S; Giannitsis, Evangelos; Gigante, Bruna; Gorog, Diana A; Jaffe, Allan S; Mair, Johannes; Möckel, Martin; Mueller, Christian; Storey, Robert F; Vilahur, Gemma; Wojta, Johann; et al. (European heart journal - acute cardiovascular care, 2021)
The formation of a thrombus in an epicardial artery may result in an acute myocardial infarction (AMI). Despite major advances in acute treatment using network approaches to allocate patients to timely reperfusion and optimal antithrombotic treatment, patients remain at high risk for thrombotic complications. Ongoing activation of the coagulation system as well as thrombin-mediated platelet activation may both play a crucial role in this context. Whether measurement of circulating biomarkers of coagulation and fibrinolysis could be useful for risk stratification in secondary prevention is currently not fully understood. In addition, measurement of such biomarkers could be helpful to identify thrombus formation as the leading mechanism for AMI. The introduction of biomarkers of myocardial injury such as high-sensitivity cardiac troponins made rule-out of AMI even more precise. However, elevated markers of myocardial injury cannot provide proof of a type 1 AMI, let alone thrombus formation. The combined measurement of markers of myocardial injury with biomarkers reflecting ongoing thrombus formation might be helpful for the fast and correct diagnosis of an atherothrombotic type 1 AMI. This position paper gives an overview of the current knowledge and possible role of biomarkers of coagulation and fibrinolysis for the diagnosis of AMI, risk stratification, and individualized treatment strategies in patients with AMI.